StMAPKK5 responds to heat stress by regulating potato growth, photosynthesis, and antioxidant defenses - Zhu, Xi; Li, Wei; Zhang, Ning; Jin, Hui; Duan, Huimin; Chen, Zhuo; Chen, Shu; Wang, Qihua; Tang, Jinghua; Zhou, Jiannan; Zhang, Yu; Si, Huaijun (Frontiers in Plant Science, 2024)
Backgrounds: As a conserved signaling pathway, mitogen-activated protein kinase (MAPK) cascade regulates cellular signaling in response to abiotic stress. High temperature may contribute to a significant decrease in economic yield. However, research into the expression patterns of StMAPKK family genes under high temperature is limited and lacks experimental validation regarding their role in supporting potato plant growth. Methods: To trigger heat stress responses, potato plants were grown at 35oC. qRT-PCR was conducted to analyze the expression pattern of StMAPKK family genes in potato plants. Plant with StMAPKK5 loss-of-function and gain-of-function were developed. Potato growth and morphological features were assessed through measures of plant height, dry weight, and fresh weight. The antioxidant ability of StMAPKK5 was indicated by antioxidant enzyme activity and H2O2 content. Cell membrane integrity and permeability were suggested by relative electrical conductivity (REC), and contents of MDA and proline. Photosynthetic capacity was next determined. Further, mRNA expression of heat stress-responsive genes and antioxidant enzyme genes was examined. Results: In reaction to heat stress, the expression profiles of StMAPKK family genes were changed. The StMAPKK5 protein is located to the nucleus, cytoplasm and cytomembrane, playing a role in controlling the height and weight of potato plants under heat stress conditions. StMAPKK5 over-expression promoted photosynthesis and maintained cell membrane integrity, while inhibited transpiration and stomatal conductance under heat stress. Overexpression of StMAPKK5 triggered biochemical defenses in potato plant against heat stress, modulating the levels of H2O2, MDA and proline, as well as the antioxidant activities of CAT, SOD and POD. Overexpression of StMAPKK5 elicited genetic responses in potato plants to heat stress, affecting heat stress-responsive genes and genes encoding antioxidant enzymes. Conclusions: StMAPKK5 can improve the resilience of potato plants to heat stress-induced damage, offering a promising approach for engineering potatoes with enhanced adaptability to challenging heat stress conditions.